Impact of the 2007-09 global economic crisis on human resource management among Chinese export-oriented enterprises - Shen, Jie; D'Netto, B. (Routledge, 2012)
This research study examines the impact of the 2007–09 global economic crisis on human resource management (HRM) practices among export-oriented enterprises in China's coastal regions. Data were obtained from 184 firms in the first phase of the study, using a structured questionnaire. In the second phase, in-depth semi-structured interviews were conducted with 18 firms. The findings of our study indicate that ‘retrenchment’ was the most common HRM strategy adopted. The global economic crisis affected all major HRM functions, but had the weakest impact on performance management. While retrenchment played an important role in cost reduction, organizational downsizing and workforce casualization are likely to have had a negative impact on long-term competitiveness and sustainability. We discuss here some effective HR strategies, such as talent acquisition, employee involvement and maintenance of employee compensation, which organizations can adopt to tide over an economic recession.